Need to simplify:

-x²y²

x½y0

I know that y0= 1 and x½ = √x

which leaves me with -x²y²

√x

x½y0

I know that y0= 1 and x½ = √x

which leaves me with -x²y²

√x

But then I am stuck.

Thanks for helping.

Need to simplify:

-x²y²

x½y0

I know that y0= 1 and x½ = √x

which leaves me with -x²y²

√x

x½y0

I know that y0= 1 and x½ = √x

which leaves me with -x²y²

√x

But then I am stuck.

Thanks for helping.

Tutors, please sign in to answer this question.

El Paso, TX

Hello John,

You are correct that y^{0} and that x^{1/2}=√x. However, in this type of problem, it is best not to convert to a square root at this step. Instead, beginning from this point:

(-x²y²)/(x½)

The rule is that if you are dividing a variable, we subtract the values for their exponents. This means that:

x^{2}/x^{1/2}

=x^{2-1/2}

=x^{3/2}

So we end up with the final answer of -x^{3/2}y^{2}

This form is generally considered the most simplified form, but if you want to express it with the square root, you can also call it:

-√(x^{3})y^{2}

- Algebra 1 4269
- Math 10849
- Algebra 5332
- Math Help 5848
- Algebra Word Problem 2629
- Word Problem 5380
- Precalculus 1733
- Algebra 2 Question 564
- Algebra Help 971
- Geometry 2097

## Comments